Drug utilization studies in neonates in a intensive care unit in a reference maternity hospital (Research, Society and Development, 2023)
The complex use of medications can result in risks for the patient, especially newborns (NB) in Neonatal Intensive Care Units (NICU). In general, NB hospitalized in the NICU make use of several drugs, most of which are classified as high-alert medications. The wide use of antimicrobials is also a reality in the NICU. The present study aims to identify, quantify and classify the drugs commonly used in neonates in the NICU, with the purpose of proposing actions on the rational use of pharmacotherapy. This is a descriptive study with a longitudinal design carried out from January to August 2020. The drugs used were classified according to the Anatomical Therapeutic Chemical (ATC) methodology. The study included 208 neonates, predominantly male (57.7%) and premature (43.3%). The mean length of stay was 40.6 days. The main reason for hospitalization was prematurity. Patients used an average of 12.8 medications, prevailing isotonic glucose 5% (87.5%), hypertonic glucose 50% (86.5) and sodium chloride 0.9% (85.1%). The main indications were electrolyte replacement, early and late sepsis. The predominant ATC groups were: blood and hematopoietic organs (B) and systemic anti-infectives (J). The high-alert medications corresponded to 28.3%. The use of drugs that act on the blood and hematopoietic organs and anti-infective drugs for systemic use was high. Actions related to controlling the use of these drugs must be carried out in order to avoid compromising patient safety and treatment effectiveness.